Pengendalian Hab Halal di Pelabuhan: Kajian Kes di Northport Malaysia - Sa’ad, Nurul Ain; Abdullah, Nor Hazana; Kamarudin, Nor Kamariah (Research in Management of Technology and Business, 2020)
Halal logistics is defined as the process of transportation, warehousing, material handling, and related activities which comply with the general principles of Sharia (Islamic law). Although there many related studies on halal logistic, studies related to the handling of Halal Hub is very limited. The handling of Halal Hub is also unclear. Therefore, this study focuses on process control work exclusively Halal Hub in Northport Malaysia and explore the factors that influence the work process control Halal Hub in Northport. This study is a single case study which focused on Northport Malaysia. Interviews and observations were used for data collection. Interviews conducted with four respondents who are experts in handling Halal Hub in Northport. Among those being interviewed were the Syariah Compliance Manager, Supervisor of the halal hub, Executive Logistic Operation and warehouse clerk in Northport. The interview data were analyzed using data reduction, data display and data conclusion. The study found that the handling of Halal Hub difficult to implement because there are no specific guidelines in implementing it. Additionally, there is less demand from the industry for Halal hub as majority of exporters in Northport are non Muslim. The low demand from industries has adverse affect on Northport in terms of costing. The investment of halal hub is not cost effective when there is no demand from industries. The process of preparing Halal Hub is also claimed to be complicated because it involves high costs and longer preparation time of halal warehouses.